Adaptive Physical Education through Aquatic Activities for Children with Motor Barriers - Daryati, Dewi; Aprilia, Imas Diana (Journal of ICSAR, 2019)
This article examines adaptive physical education through aquatic activities for children with motor barriers. This research is based on several problems faced by children with motor impairment who are not able to fully participate in physical education activities through aquatic exercises. It is caused by the inexistence of systematic and integrated guidelines to which an instructor can refer when giving aquatic exercises to children with motor delay. Adaptive physical education through aquatic activities is really helpful in optimizing motor ability of those children with motor delay. This research aims at figuring out the implementation of adaptive physical education through aquatic activities for children with motor barriers. This research applies descriptive method. Data are collected through observation, interview, literature study, and documentation. Research finding shows that there is not any special learning planning yet which is adjusted to the ability of children with motor barriers. The exercises given to children with motor barriers are made the same with general exercise program and the evaluation of the training results is not yet consistent